MicroRNAs Play a Role in Parkinson’s Disease by Regulating Microglia Function: From Pathogenetic Involvement to Therapeutic Potential - Li, Silu; Bi, Guorong; Han, Shunchang; Huang, Rui (Frontiers in Molecular Neuroscience, 2022)
Parkinson’s disease (PD) is a clinically common neurodegenerative disease of the central nervous system (CNS) caused by the degenerative loss of dopaminergic neurons in the substantia nigra striatum. Microglia (MG), as an innate immune cell in the CNS, are involved in a variety of immunity and inflammatory responses in the CNS. A number of studies have shown that the overactivation of MG is one of the critical pathophysiological mechanisms underlying PD. MicroRNAs (miRNAs) are considered to be an important class of gene expression regulators and are involved in a variety of physiological and pathological mechanisms, including immunity and inflammation. In addition, miRNAs can affect the progress of PD by regulating the expression of various MG genes and the polarization state of the MG. Here, we summarize recent articles and describe the important role of MG pathological polarization in the progression of PD, the diverse mechanisms responsible for how miRNAs regulate MG, and the potential therapeutic prospects of miRNAs for PD. We also propose that the regulation of miRNAs may be a novel protective approach against the pathogenesis of PD.